Kesehatan mental mahasiswa ditinjau dari two continua model: Pengujian multiple analysis of variance - Deasyanti, Deasyanti; Muzdalifah, Fellianti (Persona:Jurnal Psikologi Indonesia, 2021)
Abstract University student’s mental health has to get more attention because they are more vulnerable in suffering psychological problems compared to general population. The aim of this study is to figure out the prevalence of mental health status of students using the two continua model. Mental health symptoms were measured by the MHC-LF that comprised emotional well-being (?= 0,843), psychological well-being (?= 0,807), and social well-being (?= 0,831); whereas psychological distress was identified using the HSCL-25 that measured anxiety (?= 0,910) and depression (?= 0,890).  A total of 514 undergraduate students was involved using convenience sampling. The descriptive statistics showed that students are categorised as flourishing 32,10%, moderate mentally healthy 65,95%, and languishing 1,95%.  Moreover, the MANOVA test statistics found that there is a significant difference in levels of depression and anxiety between flourishing, moderate mentally healthy and languishing.  This study implies that the university should provide the mental health intervention to help students in dealing with psychological distress, and to increase their mental health into flourishing.Keywords: Mental health; Psychological distress; Two continua model; University student. AbstrakIsu kesehatan mental di kalangan mahasiswa perlu mendapat perhatian karena mahasiswa merupakan kelompok populasi yang rentan mengalami masalah psikologis. Dengan menggunakan pendekatan two continua model, penelitian ini bertujuan untuk mengetahui prevalensi tipe kesehatan mental mahasiswa. Indikator sehat mental diukur melalui kuesioner Mental Health Continuum-Long Form yang terdiri dari 3 skala: emotional well-being (?= 0,843), psychological well-being (?= 0,807), dan social well-being (?= 0,831).  Indikator psikopatologis diukur menggunakan skala Hopkins Symptom Check List-25 yang terdiri dari skala kecemasan (?= 0,910) dan skala depresi (?= 0,890). Sebanyak 514 mahasiswa menjadi responden dalam penelitian ini menggunakan teknik sampling convenience. Dengan analisis statistik deskriptif diketahui 32.10% mahasiswa termasuk dalam kategori sehat mental flourishing, 66,95% moderate mentally healthy dan 1,95% languishing. Uji statistik MANOVA menemukan perbedaan tingkat kecemasan dan depresi antara kelompok sehat mental yang berbeda. Implikasi hasil penelitian ini terkait dengan program intervensi kesehatan mental mahasiswa yang bersifat kuratif, protektif, maupun promotif untuk meningkatkan keberfungsian psikologis secara lebih optimal. Kata kunci: Distres psikologis; Mahasiswa; Sehat mental; Two Continua Model